Adaptation and Validation of the Texas Revised Inventory of Grief—Present Scale - Rocio Luana Gruppi; Cecilia Yaccarini; Agustin Freiberg Hoffmann; Andrew Futterman; Hugo Simkin (Health Psychology Research)
This study aims to evaluate the psychometric properties and internal consistency of the Spanish version of the Texas Revised Inventory of Grief- Present \[TRIG-Present\] in Buenos Aires, Argentina, which assesses a series of thoughts, emotions and behaviors in losses related to the present. A total of 285 adults participated in the study with ages between 18 and 80 years (M = 55.09, SD = 15.27) and both sexes (Men = 42.8%, Women = 57.2%). The three-factor model resulted in acceptable fit indices (TLI = .970; CFI = .976; SRMR = .064). The results indicated an acceptable internal consistency for Emotional Response (ω = .850), Not Acceptance (ω = .816) and Thought (ω = .837). The spanish adaptation of the TRIG-Present presents 13 items proposed by the original authors.